2008
DOI: 10.1143/jjap.47.4007
|View full text |Cite
|
Sign up to set email alerts
|

Development of an X-Band Filter Using Air-Gap-Type Film Bulk Acoustic Resonators

Abstract: We have developed an X-band filter utilizing air-gap-type film bulk acoustic resonators (FBARs). The air-gap structure is simple and cost-effective. Results from both simulations and experiments demonstrate that a dome-shaped air gap was formed between the substrate surface and the bottom electrode and that an air-gap-type FBAR structure was possible. The air gap can be formed on the flat substrate using stress control of piezoelectric and metal films without using a thick sacrificial layer. As a result, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…As the resonance frequency of the resonator is determined by the thickness of the AlN layer, there is essential interest of using ultrathin 100-200 nm films to extend the current FBAR technology from 1-2 to 5-10 GHz range. 4 AlN-based solidly mounted BAW resonators for 10 GHz applications require AlN films having thickness as low as approximately 160 nm. 5 Thinner AlN layers are also of strong interest for temperature compensated Lamb wave resonators 6 as it has been shown that for thin AlN layers ͑100-200 nm͒ the temperature coefficient of frequency can be compensated over a very wide frequency range enabling temperature compensation of resonators operating at multiple frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…As the resonance frequency of the resonator is determined by the thickness of the AlN layer, there is essential interest of using ultrathin 100-200 nm films to extend the current FBAR technology from 1-2 to 5-10 GHz range. 4 AlN-based solidly mounted BAW resonators for 10 GHz applications require AlN films having thickness as low as approximately 160 nm. 5 Thinner AlN layers are also of strong interest for temperature compensated Lamb wave resonators 6 as it has been shown that for thin AlN layers ͑100-200 nm͒ the temperature coefficient of frequency can be compensated over a very wide frequency range enabling temperature compensation of resonators operating at multiple frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Inserting equation (3) and (8) into (7) yields the following: (9) Reaction (6) is the dominant process during ozone sensing, thus (10) Therefore, the calculated power law exponent n, defined as d(logΔf)/d(logPO 3 ) is (11) where m is sufficiently large under usual conditions [17]. Thus n is around -1, which means the relationship between resonant frequency and ozone concentration is hyperbolic, which is in agreement with the experimental results (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A resonance condition occurs if the thickness of piezoelectric thin film is equal to an integer multiple of a half of the acoustic wavelength. In recent years, FBARs have been developed to be radio frequency electrical filters [11] as well as high sensitivity mass, ultraviolet and humidity sensors [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…FBAR has been well developed both as filters [4] and as high sensitivity mass sensors [5] in recent years. The schematic structure of the FBAR RH sensor is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%